2004
DOI: 10.1074/jbc.m404466200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glucosylceramide Synthase Does Not Reverse Drug Resistance in Cancer Cells

Abstract: The multidrug-resistant cancer cell lines NCI/AdR RES and MES-SA/DX-5 have higher glycolipid levels and higher P-glycoprotein expression than the chemosensitive cell lines MCF7-wt and MES-SA. Inhibiting glycolipid biosynthesis by blocking glucosylceramide synthase has been proposed to reverse drug resistance in MDR cells by causing an increased accumulation of proapoptotic ceramide during treatment of cells with cytotoxic drugs. We treated both multidrug-resistant cell lines with the glucosylceramide synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 46 publications
(61 reference statements)
3
44
1
1
Order By: Relevance
“…In general, the assumption has been that the sensitizing effect was due to inhibition of GCS, thereby resulting in increased ceramide levels and induction of apoptosis. However, recent studies suggest that the chemosensitizing effect of PDMP and its analogues may not be related to GCS inhibition (25)(26)(27). Iminosugar-based GCS inhibitors which are from a different chemical class than the ceramide-based inhibitor PDMP were observed to be ineffective in chemosensitizing multidrug-resistant tumor cells (25).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the assumption has been that the sensitizing effect was due to inhibition of GCS, thereby resulting in increased ceramide levels and induction of apoptosis. However, recent studies suggest that the chemosensitizing effect of PDMP and its analogues may not be related to GCS inhibition (25)(26)(27). Iminosugar-based GCS inhibitors which are from a different chemical class than the ceramide-based inhibitor PDMP were observed to be ineffective in chemosensitizing multidrug-resistant tumor cells (25).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds, which seem to be more specific and less toxic, did not sensitize multidrug-resistant tumor cells to cytostatics (9,12). NorrisCervetto et al (9) concluded from their studies that the effect of PDMP on drug resistance could not be explained by inhibition of GCS alone. However, there are no studies providing a mechanism unrelated to GCS inhibition by which PDMP could chemosensitize multidrug-resistant tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…10,11). It was observed that iminosugars, which are potent inhibitors of GCS, do not chemosensitize multidrug-resistant tumor cells to cytostatics (9,12). The notion thus arises that chemosensitization achieved by PDMP may not involve GCS but instead is caused by an alternative mechanism.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Високоефективну рідинну хроматографію проводили за методикою, опи-саною у [21][22][23]. Зразки для ВЕРХ аналізу готували таким чином: клітини відми-вали двічі у ЗФР, осад ресуспендували у 100 мкл ЗФР, додавали 200 мкл дейоні зованої води і проводили три цикли заморожування/розтавання.…”
Section: B4galnt1unclassified